Residual dysplasia of the hip after successful ultrasound-monitored treatment: how does an infant's hip evolve?. Issue 6 (3rd May 2022) - Dornacher, Daniel; Lutz, Bernd; Freitag, Tobias; Sgroi, Mirco; Taurman, Rita; Reichel, Heiko
Abstract : Despite that normal values for the hip joint are reached at the end of ultrasound-monitored-treatment, the development of the acetabulum can be compromised during the growth phase. The acetabular index (AI) measured on a pelvic radiograph has been proven to be a reliable parameter. The aim of this study is to gain a better understanding of the dynamics of once-treated, residually dysplastic hips. This should be achieved by radiographically following these hips up to a milestone-examination at the end of preschool age. A total of 120 hips of consecutive 60 infants were included in this examination, each presenting with a residual developmental dysplasia of the hips (DDH) after successful ultrasound-monitored harness treatment. Radiographic follow-up was assessed retrospectively around 18 months, 3 years and 6 years of age, and the AI was measured. The age-dependent Tönnis classification was applied. The hips were assigned normal, mildly or severely dysplastic. Dependent t -test for paired samples indicated a highly significant improvement of the AI-values, including from the first to the second and from the second to the third follow-up. The percentage distribution into the Tönnis classification changed remarkably: in the first follow-up, 36 of the 120 hips were evaluated 'severely dysplastic', in the third follow-up only 1. On the other hand, three hips underwent acetabuloplasty. Even after normal values have been achieved at the end of ultrasound-monitored treatment, there remains a risk of residual dysplasia of the hips. Particularly, when the first radiographic examination shows nonphysiological findings, further close-meshed follow-up is recommended. Level of evidence: retrospective study of therapeutic outcome, consecutive patients, level II.